TINDAK TUTUR DIREKTIF ANAK AUTIS - Endang Sumarti; Umi Salamah (LITERA, 2015)
AbstractThis study aims to describe forms, functions, and strategies in autistic children’sdirective speech acts. The data were from the recording of dialogs performed in anautism-specific school and an inclusive school in Malang City. They were collectedthrough observations and recording. The data collection and analysis were interactively,simultaneously, and iteratively done to deeply and wholly understand forms, functions,and strategies in autistic children’s directive speech acts. The results of the study areas follows. First, the forms include requests, commands, and prohibitions. Second, thefunctions comprise those of requesting, commanding, and prohibiting. Third, the strategiesconsist of a direct strategy and an indirect strategy.